International Conference on the Future of Tourism (ICFT) (2019)
The paradigm of sustainable tourism is partly based on the idea that visitor attitudes, choices and behaviour about the environment critically influence sustainability. Biological gardens are traditional sites for nature-based tourism attracting large volume of visitors. The environmental attitudes of these visitors are however rarely studied. This study therefore examined the environmental attitudes of visitors to a nature based tourism destination in Nigeria, specifically Obafemi Awolowo Biological Garden. The New Environmental Paradigm scale consisting of 12 factors was employed. A total of 383 copies of structured questionnaire were administered to visitors and analysed. Visitors showed high percentage agreement with the factors; ‘humans have the right to modify the natural environment to suit their needs’, and ‘mankind was created to rule over the rest of nature’. They displayed the highest percentage disagreement with the factors; ‘humans need not adapt to the natural environment because they can remake it to suit their needs’, and ‘we are approaching the limit of the number of people the earth can support’. Visitors to the garden displayed anthropocentric beliefs and human dominance over the rest of nature.